Taxonomic and palaeobiological assessment of the South African mosasaurids - Woolley, Megan Rose (Department of Biological Sciences, 2021)
South African mosasaur remains consist of a frontal with articulating portions of the parietal and postorbitofrontals (SAM-PK-5265); two dentary fragments (SAM-PK-5265) assigned to ‘Tylosaurus capensis' by Broom in 1912 (SAM-PK-5265); an undescribed muzzle unit and associated isolated teeth (CGP/1/2265) from Pondoland and a more recently discovered isolated partial vertebra from St Lucia. Some research has been done on the material, but there is still uncertainty concerning their relationships and taxonomy. This research aims to provide a taxonomic assessment of all the SA mosasaurid material to better understand their phylogenetic relationships and to place them in the context of mosasaurs from other parts of Africa and globally. In addition, isotopic analyses, micro-computed tomography (micro-CT), mineralised tissue histology and scanning electron microscopy (SEM) are applied to the SA mosasaur remains to decipher various aspects of their palaeobiology. This study identifies three mosasaur taxa from SA: Mosasaurus sp., cf. M. hoffmannii., cf. Taniwhasaurus, and cf. Prognathodon. The isolated vertebra is assigned to Mosasaurus sp., cf. M. hoffmannii. The frontal and dentary fragments (SAM-PK-5265) originally described as Tylosaurus appears to be a mix of two taxa: One of the dentary fragments possesses replacement teeth with enamel ornamentation that resembles, Ta. mikasaensis, but is tentatively assigned to cf. Taniwhasaurus based on tooth recurvature. The other dentary fragment and a frontal with articulated elements are suggested to belong to the same individual as the muzzle unit for which the suggested assignment is cf. Prognathodon. Strontium analysis of tooth enamel dated the cf. Prognathodon material to the end of the Maastrichtian (87Sr/86Sr = 0.707817; age = 66.85Ma). The cf. Taniwhasaurus dentary fragment is likely Santonian-aged, as originally indicated in 1901. SEM of enamel from cf. Prognathodon reveals a complex array of prismless enamel types and pervasive aggregations of fossilised bacteria in the underlying dentine. The δ18OPO4 derived body temperature estimate (Tb) of the cf. Prognathodon (Tb = 33.21°C) compares well with previously reported Tb for mosasaurs and may indicate that the mosasaur was capable of maintaining a Tb higher than that of the surrounding seawater.